Pola Pemberdayaan Masyarakat Berbasis Digital, Inklusif, dan Stabil Pasca Covid-19: Bibliometrik Analisis - Kususiyanah, Anjar; Wahid, Soleh Hasan (Proceedings of Annual Conference on Community Engagement, 2022)
New formula and solutions are needed in the community empowerment process for sustainable economic recovery after the Covid-19 pandemic. This essay proposes a formula for green, digital, inclusive, and stable community empowerment. A bibliometric investigation of Covid-19 papers on community empowerment found this formula. Bibliometric analysis is used to develop plans for government, academia, and universities. Bibliometric analysis starts by determining empowerment program aims in selected papers. Identify the program's form. Third, articles are mapped for community empowerment initiatives, targets, and areas. Finally, the identification results are used to choose the best model for community economic empowerment. The COVID-19 pandemic targets MSMEs and the tourism sector for community empowerment. The majority's empowerment concepts focus on marketing, digital marketing, and online soft skills. In this situation, community service should focus on financial capacities, business management, government legislation, and the halal sector. In Covid-19, most community empowerment is done online, which has been shown to benefit MSMEs. Local governments may empower MSMEs with this successful online method.